Least Error Squares Approach: A Practical Method for Power System Frequency and Amplitude Estimation. (2016) - Sharma, R.B.; Dhole, G.M.
Abstract: Deregulation, competitive electricity market, expansion of transmission and distribution network, increased applications of power electronics make the power system more complex and the determination of accurate power system frequency becomes more difficult. The algorithm based on the Taylors series expansion principle of the least error squares curve fitting technique for measuring the practical frequency at a power system bus is presented in this paper. The algorithm was tested practically in laboratory and results are presented in this paper. The effect of data window size, sampling frequency, time reference selection and Taylor's series expansion on the performance of the algorithm are also discussed in this paper.